2018
DOI: 10.5650/jos.ess18026
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Bactericidal Effects of Hydrophobic Lung Surfactant Proteins and Their Peptide Mimics Using Liposome Molecular Trojan

Abstract: Lung surfactant, besides alveolar stability, also provides defence against pathogens by surfactant proteins (SP), SP-A and SP-D. The hydrophobic proteins SP-B and SP-C enhance surface activity. An unusual and paradoxical effect of bovine LS and synthetic model LS with SP-B/-C was bactericidal to Staphylococcus aureus and Escherichia coli. Bacterial proliferation were investigated with bovine lung surfactant extract (BLES), dipalmitoylphosphatdylcholine, palmitooleylglycerol, in combination with SP-B/-C using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 76 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…The amino acid sequence of the viral RdRp was scanned for identification of known functional domains/motifs using InterPro Scanner (Hunter, Apweiler et al 2009). Homology modeling of the RdRp was carried out using SwissModel and quality was checked using PROCHECK (Dutta, Nag et al 2018). Rigid-body molecular docking between several established antiviral drugs and RdRp from SARS-CoV-2 was carried out using AutoDock (v4.2), (Dutta, Shityakov et al 2018).…”
Section: Data Sampling and Analysismentioning
confidence: 99%
“…The amino acid sequence of the viral RdRp was scanned for identification of known functional domains/motifs using InterPro Scanner (Hunter, Apweiler et al 2009). Homology modeling of the RdRp was carried out using SwissModel and quality was checked using PROCHECK (Dutta, Nag et al 2018). Rigid-body molecular docking between several established antiviral drugs and RdRp from SARS-CoV-2 was carried out using AutoDock (v4.2), (Dutta, Shityakov et al 2018).…”
Section: Data Sampling and Analysismentioning
confidence: 99%
“…This model is adopted in several recent reports. 13,[27][28][29] In the MARTINI model, each amino acid is represented by a single bead that can be polar (sL), non-polar (sH) or neutral (tN). The sL and sH beads are mutually repulsive and differ only in the parameterization of their respective dihedral potentials.…”
Section: Coarse-grained Modelmentioning
confidence: 99%
“…Their simulation results revealed that, when brought into contact with pulmonary surfactant, silver and polystyrene nanoparticles are immediately covered with a biomolecular corona composed of both lipids and proteins. In another recently published paper, K. Dutta et al 29 studied the paradoxical bactericidal effects of hydrophobic lung surfactant proteins and their peptide mimics using a molecular Trojan horse liposome. This study has alarming implications in using high dosage exogenous surfactant for treatment of respiratory distress syndrome, genetic knock-out abnormalities associated with these proteins, and the novel roles played by SP-B/C as bactericidal agents.…”
Section: Introductionmentioning
confidence: 99%
“…Homology modeling of the RdRp was carried out using SwissModel and quality was checked using PROCHECK [16]. Rigid-body molecular docking between several established antiviral drugs and RdRpSARS-CoV-2 was carried out using AutoDock (v4.2), [14].…”
Section: Data Sampling and Analysismentioning
confidence: 99%